LABOR MANAGEMENT COMMITTEE BUDGET PROPOSALS (Tufts Archival Research Center, 2007)
MARGINALIA; Budget proposal from 1994 by Labor Management Committee. Compares proposals by Curtis with amounts approved in both December and January by the Tobacco Industry. Indicates revised/adjusted proposed amounts by Curtis in April.